Implementación de un sistema de costos por procesos en la producción de Banano Orgánico para mejorar la rentabilidad de la Asociación de Pequeños Agricultores y Ganaderos El Algarrobal de Moro - Terrones León, Uver Yon (2016)
The present investigation has for objective to implement a System of Costs for Processes in the Production of Organic Banana tree to improve the Profitability of the Association of Small Farmers and Cattlemen Algarrobal of Moorish. For the development of the investigation the descriptive method, the information has been applied taken directly of the reality it has been structured, analyzed and explained through technical of gathering and treatment of information like the observation, the documental analysis, tabulation of squares and the formulation of graphics. The population and the sample object of this investigation is determined by the Association of Small Farmers and Cattlemen Algarrobal of Moorish. The results of the investigation demonstrate that the Implementation of a System of Costs for Processes doesn't improve the Profitability of the Association of Small Farmers and Cattlemen Algarrobal of Moorish.